Magic, Modernity, and Race in Seychelles: The Situation of Grigri in the Modern Creole Order - Palmyre, Michael Gilbert George (Curtin University, 2023)
In 1977, a socialist coup d'etat in Seychelles instituted an era of anti-colonial, anti-capitalist, and pro-African Creole nationalism. One aspect of Creoleness – witchcraft, or ‘grigri’ – was excluded from the Creole canon. Using grigri as a lens through which to examine modernity and race in Seychelles, this ethnographic research explores how grigri has signified a pre-modern blackness and how Creole people have responded to such colonial logics.